2018
DOI: 10.5944/reop.vol.28.num.3.2017.21617
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad de un programa de mejora de competencias profesionales en resolución de conflictos/Effectiveness of a programme on the improvement of professional skills for conflict resolution

Abstract: RESUMENLa formación permanente del profesorado es un factor clave en la calidad educativa. El desarrollo de programas eficaces parte de la consideración de condicionantes internos y externos en el diseño del mismo. En ese sentido, diseñar procesos de formación permanente supone tener en cuenta factores diversos, que encaminan un resultado favorable en la adquisición de competencias en los participantes. Este trabajo tiene como objetivo aportar un programa válido para la adquisición de competencias en resolució… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Moreover, "efforts should develop suitable teacher-training programmes on how to address conflicts, making teachers aware that they themselves can be the source of the emerging conflict" (Larsson et al, 2021, p. 800). Thus, it is urgent to raise the need for teacher training in both initial and in-service training to improve their social and emotional competencies (Bisquerra-Alzina & García-Navarro, 2018;Galindo-Domínguez et al, 2022;Olmos-Migueláñez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, "efforts should develop suitable teacher-training programmes on how to address conflicts, making teachers aware that they themselves can be the source of the emerging conflict" (Larsson et al, 2021, p. 800). Thus, it is urgent to raise the need for teacher training in both initial and in-service training to improve their social and emotional competencies (Bisquerra-Alzina & García-Navarro, 2018;Galindo-Domínguez et al, 2022;Olmos-Migueláñez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to the review conducted by Hakvoort et al (2019), this negativist approach, focused on examining and correcting inappropriate student behaviour, was predominant until the first decade of the 21st century. Not surprisingly, Merma- Molina et al (2019), examining 806 plans from all Spanish communities, found that most coexistence plans carried out at schools, lacking an adequate diagnosis, have focused almost exclusively on students (Olmos-Migueláñez et al, 2017). However, since the second decade, they have been shifting their course towards the needs of schools, taking all members of the educational community into account (Grau-Vidal et al, 2016;Hernández-Prados et al, 2020).…”
Section: Introduction and Objectivesmentioning
confidence: 99%